2014
DOI: 10.1038/ismej.2014.41
|View full text |Cite|
|
Sign up to set email alerts
|

Natural occurrence of microbial sulphur oxidation by long-range electron transport in the seafloor

Abstract: Recently, a novel mode of sulphur oxidation was described in marine sediments, in which sulphide oxidation in deeper anoxic layers was electrically coupled to oxygen reduction at the sediment surface. Subsequent experimental evidence identified that long filamentous bacteria belonging to the family Desulfobulbaceae likely mediated the electron transport across the centimetre-scale distances. Such long-range electron transfer challenges some long-held views in microbial ecology and could have profound implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
257
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(280 citation statements)
references
References 36 publications
22
257
1
Order By: Relevance
“…Although it has been suggested that filaments of cells closely related to Desulfobulbus species accounted for conductivity to reduced marine sediments from Aarhus Bay, it is, in fact, unknown whether this is possible because the conductivity of the filaments was not demonstrated (Pfeffer et al, 2012;Reguera, 2012;Malkin et al, 2014). No long bacterial filaments were observed in the Nantucket sediments used in these studies.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Although it has been suggested that filaments of cells closely related to Desulfobulbus species accounted for conductivity to reduced marine sediments from Aarhus Bay, it is, in fact, unknown whether this is possible because the conductivity of the filaments was not demonstrated (Pfeffer et al, 2012;Reguera, 2012;Malkin et al, 2014). No long bacterial filaments were observed in the Nantucket sediments used in these studies.…”
mentioning
confidence: 57%
“…The suppression of sediment conductivity with oxidation indicated that long-range electron transport through the sediments is significantly different than that through G. sulfurreducens biofilms. It is unknown how oxidizing conditions might have an impact on the previously proposed conductivity through filamentous bacteria (Pfeffer et al, 2012;Malkin et al, 2014) because the hypothesized conductivity and the mechanisms for conduction have not been documented (Reguera, 2012). …”
mentioning
confidence: 99%
“…Moreover, electrogenic sulfur oxidation appears to be competitively successful over other microbial sulfur oxidation strategies in laboratory experiments when organic-rich coastal sediments are incubated with oxygenated overlying water (5,9). The geochemical signature of long-distance electron transport and the associated cable bacteria has also been found under natural conditions in a range of coastal habitats with organic-rich sediments (8). A literature survey combined with data mining from 16S rRNA gene sequence archives suggested that electrogenic sulfur oxidation has a cosmopolitan distribution, occurring in a range of organic rich areas, including aquaculture-impacted areas, coastal mud plains, salt marshes, seasonally hypoxic basins, mangrove swamps, and cold seeps.…”
mentioning
confidence: 90%
“…In sediments with high rates of sulfate reduction, all detectable free sulfide can be removed by this process from a suboxic zone up to about 30 mm (5,7,8). Moreover, electrogenic sulfur oxidation appears to be competitively successful over other microbial sulfur oxidation strategies in laboratory experiments when organic-rich coastal sediments are incubated with oxygenated overlying water (5, 9).…”
mentioning
confidence: 91%
“…It also does not enable the evaluation of the electrochemical behavior of those compounds present beyond the WE's boundary layer (Bard and Faulkner, 2001). Since both electron accepting (anodic) and electron donating (cathodic) reactions may concurrently occur within close proximities where EET prevails (Malkin et al, 2014), using a single WE for the evaluation of electron mediators in microbial systems may not be ideal.…”
Section: Introductionmentioning
confidence: 99%